2007
DOI: 10.1208/pt0803061
|View full text |Cite
|
Sign up to set email alerts
|

Development of a bladder instillation of the indoloquinone anticancer agent EO-9 using tert-butyl alcohol as lyophilization vehicle

Abstract: The purpose of this research was to develop a stable bladder instillation of EO-9 for the treatment of superficial bladder cancer. First, stability and dissolution studies were performed. Subsequently, the freeze-drying process was optimized by determination of the freeze-drying characteristics of the selected cosolvent/water system and differential scanning calorimetry analysis of the formulation solution. Furthermore, the influence of the freeze-drying process on crystallinity and morphology of the freeze-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…9 TBA is a popular organic cosolvent for freeze-drying poorly water-soluble pharmaceuticals. 10 In addition to enhancing solubility, the use of TBA reduced the drying times and enabled the freeze-drying of lipophilic drugs. Notable commercial examples are prostaglandin E-1 (Caverject, Pharmacia and Upjohn Inc., MI), 11 prepared by freeze-drying from a 20% w/w TBA solution and bendamustine hydrochloride (Treanda, Cephalon Inc., PA).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 TBA is a popular organic cosolvent for freeze-drying poorly water-soluble pharmaceuticals. 10 In addition to enhancing solubility, the use of TBA reduced the drying times and enabled the freeze-drying of lipophilic drugs. Notable commercial examples are prostaglandin E-1 (Caverject, Pharmacia and Upjohn Inc., MI), 11 prepared by freeze-drying from a 20% w/w TBA solution and bendamustine hydrochloride (Treanda, Cephalon Inc., PA).…”
Section: ■ Introductionmentioning
confidence: 99%
“…TBA is a popular organic cosolvent for freeze-drying poorly water-soluble pharmaceuticals . In addition to enhancing solubility, the use of TBA reduced the drying times and enabled the freeze-drying of lipophilic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Residual tert-butanol and ethanol were determined by gas chromatography (GC) as described earlier (Van der Schoot et al, 2007). Fifty mg per sample was dissolved in 5 mL DMSO in triplicate.…”
Section: Residual Tert-butanol and Residual Ethanolmentioning
confidence: 99%
“…Recurrence‐free rates were good in comparison with the results of other ablative studies (Hendricksen et al ., 2009; Jain et al ., 2009). EO9 was reformulated in 2007 (van der Schoot et al ., 2007a; 2008; van der Schoot et al ., 2007b), and it is currently undergoing phase III clinical evaluation in several centres across North America and Europe. Additionally, studies where EO9 was administered within 24 h of TUR, which is the standard recommended treatment for superficial TCC of the bladder (Sylvester et al ., 2004), demonstrated that EO9 was well tolerated and has a good safety profile (Hendricksen et al ., 2008).…”
Section: Pharmacology Of Eo9mentioning
confidence: 99%